ANALYSIS OF POTENCY AND PROBABILITY OF SUBSECTOR DEVELOPMENT OF MARINE FISHERIES CAPTURE IN MALANG REGENCY - Mochammad Fattah; Tiwi Nurjannati Utami; Candra Adi Intyas (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
This study objectives to analyze the estimated development of the production of the fish catches, analyze the factors which affect on the production amount, and to analyze the base or non bases are on Malang Regency. The method used is quantitative and the type of secondary data from BPS and DKP with documentation collecting technique. Quantitative data analysis of this research are quadratic trend, multiple linear regression and LQ. The calculation shows that marine fisheries catches production has increased an average of 6.5%. Factors that affecting of the production increase are the number of fishing vessel and fishermen amount. While the average value of LQ during the last 5 years shows that Sumbermanjing Subdistrict is a base region so it has the opportunity to develop. Keywords: production, sea fish, estimation, influence, base